Metabolic fingerprinting of gilthead seabream (Sparus aurata) liver to track interactions between dietary factors and seasonal temperature variations - Tomé S. Silva; Ana M.R. da Costa; Luís E.C. Conceição; Jorge P. Dias; Pedro M.L. Rodrigues; Nadège Richard (PeerJ, 2014)
Farmed gilthead seabream is sometimes affected by a metabolic syndrome, known as the “winter disease”, which has a significant economic impact in the Mediterranean region. It is caused, among other factors, by the thermal variations that occur during colder months and there are signs that an improved nutritional status can mitigate the effects of this thermal stress. For this reason, a trial was undertaken where we assessed the effect of two different diets on gilthead seabream physiology and nutritional state, through metabolic fingerprinting of hepatic tissue. For this trial, four groups of 25 adult gilthead seabream were reared for 8 months, being fed either with a control diet (CTRL, low-cost commercial formulation) or with a diet called “Winter Feed” (WF, high-cost improved formulation). Fish were sampled at two time-points (at the end of winter and at the end of spring), with liver tissue being taken for FT-IR spectroscopy. Results have shown that seasonal temperature variations constitute a metabolic challenge for gilthead seabream, with hepatic carbohydrate stores being consumed over the course of the inter-sampling period. Regarding the WF diet, results point towards a positive effect in terms of performance and improved nutritional status. This diet seems to have a mitigating effect on the deleterious impact of thermal shifts, confirming the hypothesis that nutritional factors can affect the capacity of gilthead seabream to cope with seasonal thermal variations and possibly contribute to prevent the onset of “winter disease”.